2021
DOI: 10.3390/pathogens10020164
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Features in Sheep with IgG and IgM Antibodies against Borrelia burgdorferi sensu lato

Abstract: Exposure of sheep to Borreliaburgdorferi sensulato (s.I.) complex, the causative agent of Lyme borreliosis (LB), has been reported in tick-abundant areas worldwide, while no data have been reported in Greece. The aim of the study was to identify the hematological alterations in sheep with seropositivity against Borrelia burgdorferi (s.I.). Blood samples were obtained from 318 tick infested sheep for blood analysis and serological determination of IgG and IgM antibodies against B. burgdorferi by indirect immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 69 publications
(88 reference statements)
0
8
0
Order By: Relevance
“…Our findings are in agreement with the previous observations in sheep seropositive for B. burgdorferi s.l. in the 2021 study by Athanasiou et al [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are in agreement with the previous observations in sheep seropositive for B. burgdorferi s.l. in the 2021 study by Athanasiou et al [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…An IFA assay was performed for the detection of IgG and IgM antibodies against B. burgdorferi s.l. and IgG antibodies against A. phagocytophilum in serum as described previously [ 21 , 38 ]. Titers ≥ 1:64 for B. burgdorferi s.l.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, serological studies conducted in animals from Turkey and Bulgaria have reported seropositivity against Borrelia burgdorferi sensu lato in rodents [ 20 , 21 ], cats [ 22 , 23 ], dogs [ [24] , [25] , [26] , [27] ], and horses [ 24 , 28 , 29 ]. In Greece, serological studies have reported a low seroprevalence (up to 2.2%) in dogs [ 5 , 6 ] but a significant seropositivity of 23.6% in sheep as reported in a study from 318 tick-infested sheep [ 4 ].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…In addition, few serological studies have been conducted in animals from Greece, suggesting the possibility of Borrelia spp. presence in the country [ [4] , [5] , [6] ]. To our knowledge, physicians in Greece associate Lyme disease only with B. burgdorferi infection, as studies in the 1990s, based on enzyme-linked immunosorbent assay (ELISA), suggested the existence of B. burgdorferi [ 7 ].…”
Section: Introductionmentioning
confidence: 99%